Low Concentrations of Corticosterone Exert Stimulatory Effects on Macrophage Function in a Manner Dependent on Glucocorticoid Receptors - He-Jiang Zhong; Hai-Yan Wang; Ce Yang; Jian-Yun Zhou; Jian-Xin Jiang (International Journal of Endocrinology)
Endogenous glucocorticoids (GCs) have both stimulatory and suppressive effects on immune cells depending on the concentration. However, the mechanisms underlying the stimulatory effects of GCs remain elusive. Rat peritoneal macrophages were treated with different concentrations of corticosterone (0, 30 nM, 150 nM, and 3 μM). To inhibit the glucocorticoid receptor (GR) activity, macrophages were preincubated with the GR antagonist RU486 (mifepristone, 10 μM) for 30 min before treatment with corticosterone (150 nM). In the absence of immune stimuli, the chemotactic and phagocytic activities of macrophages were markedly enhanced by low concentrations of corticosterone (30 and 150 nM) when compared with vehicle-treated controls. However, these effects were not observed at a high concentration of corticosterone (3 μM). Furthermore, blocking GR activity inhibited 150 nM corticosterone-enhanced chemotaxis and phagocytosis of macrophages. Meanwhile, after treatment with corticosterone (150 nM) for 1 h and 3 h, GR protein expression increased to 1.4- and 2.2-fold, respectively, compared to untreated macrophages. These effects were inhibited by RU486. However, mineralocorticoid receptor (MR) protein expression was not influenced by 150 nM corticosterone. These results demonstrate that low concentrations of corticosterone exert stimulatory effects on macrophage function in the absence of immune stimuli, and GR is at least partially responsible for these effects.